RFID 기반 물류 관리의 적용 효과 분석 - 커튼월 공사를 중심으로 - 윤수원; 진상윤; 김예상; Yoon, Su-Won; Chin, Sang-Yoon; Kim, Yea-Sang (한국건설관리학회 논문집, 13(1), 2012)
RFID-based logistics is increasingly adopted in various areas of the construction industry as a technology that can improve effectiveness and efficiency of construction logistics. However, the technology is not widely adopted yet compared to the potential of RFID applications in the construction industry that the existing research has shown. Since the validation and verification of the benefit from RFID applications were biased toward the productivity of managers, more wide aspect of validation and verification is necessary. Therefore, the objective of this paper is to show how much impact the RFID-based logistics management system can have on resource leveling and allocation that have a direct impact on a construction project as well as the managers' productivity improvement that was shown by the existing research. This paper also discusses issues arisen during the test process. RFID 기반의 물류 관리는 건설 프로젝트의 효과적인 물류 관리를 위해 적용이 모색되는 기술로, 점차 다양한 분야로 기술 적용이 확대되고 있다. 하지만 기존의 연구들에서 지적하고 있는 바와 같이, RFID 기술이 가지는 잠재적 가능성에 비해 기술의 확산이 미흡한 상태에 있고, 이를 위한 적용 효과에 대한 검증이 관리자의 생산성 향상에 치우쳐져 있어, 보다 폭넓은 관점에서의 효과 검증이 필요한 상태에 있다. 따라서 본 연구에서는 RFID 기반의 물류관리 시스템의 보다 정확한 효과 검증을 위해, 실제 프로젝트의 커튼월 공사를 대상으로 시스템을 적용/운영하고, 현장 및 시스템 모니터링을 통해 적용효과 및 시사점을 제시하였다. 그리고 본 연구에서 제시한 RFID 기반 물류 관리 시스템의 적용효과는 기존 연구에서 제시하고 있는 관리자의 업무 시간 단축 및 생산성 향상과 관련된 효과뿐만 아니라, 물류 및 작업 생산성에 영향을 미치는 자원 평준화 측면에서의 효과를 포함하고 있으며, 기존 연구와는 달리 가장 유사한 환경을 가지는 쌍둥이 빌딩을 대상으로 RFID 적용 및 미적용 사례를 분석하여, 보다 정확한 비교 데이터를 제시하였다는데 의의를 가진다.